PENGGUNAAN GAYA BAHASA SINDIRAN DALAM TAYANGAN KONTEN ORMAS PADA KANAL YOUTUBE DEDDY CORBUZIER: The Use of Sarcastic Language in the Content of Mass Organisations on Deddy Corbuzier's YouTube Channel - Sasmita, Nur; Mayong; Saleh, Muhammad (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study aims to describe the form and function of satirical language found in Ormas content on Deddy Corbuzier's Youtube channel. This study uses a qualitative descriptive method with data sources in the form of Ormas episodes 1–3 from 2023. Data was collected through observation and note-taking techniques, with the researcher as the primary instrument (human instrument). Data analysis was conducted through the stages of reduction, presentation, and conclusion drawing. The results of the study show that there are five forms of satirical language styles, namely irony, cynicism, sarcasm, satire, and innuendo. The functions of each satirical language style include mocking, criticising, reprimanding, and raising awareness. Overall, the use of satirical language styles in Ormas broadcasts serves as a means of social criticism and reflection on the social phenomena raised in the content.